Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Please help if you can. Thank you

Please Help If You Can Thank You class=

Sagot :

s1m1

Answer:

Step-by-step explanation:

x-4 = log (base3) of 6; add 4 to both sides

x= [log (base3) of (2*3) ] +4; split 6 to 2*3

x= [log (base 3) of 3 + log ( base 3) of 2] + 4; use rule log(ab) = log a+log b

x= log (base 3) of 2 + 1+ 4; use rule log (base a) of a = 1

x= log (base 3) of 2 + 5; put in the calculator

x≈5.63